2016
DOI: 10.1016/j.ultsonch.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic enhancement of the simultaneous removal of quaternary toxic organic dyes by CuO nanoparticles loaded on activated carbon: Central composite design, kinetic and isotherm study

Abstract: Copper oxide nanoparticles loaded on activated carbon (CuO-NPs-AC) were prepared and fully analyzed and characterized with FE-SEM, XRD and FT-IR. Subsequently, this novel material was used for simultaneous ultrasound-assisted adsorption of brilliant green (BG), auramine O (AO), methylene blue (MB) and eosin yellow (EY) dyes. Problems regard to dyes spectra overlap in quaternary solution of this dyes were omitted by derivative spectrophotometric method. The best pH in quaternary system was studied by using one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 165 publications
(52 citation statements)
references
References 64 publications
1
51
0
Order By: Relevance
“…The CuO nanoparticles completely disintegrated the Acid Black 210 dye into CO 2 and H 2 O within one hour. The high disintegrative capacity of the CuO nanoparticles is due to their crystalline nature, because studies have shown that the higher the crystalline nature, the higher the disintegrative ability and the disintegration rate [2,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CuO nanoparticles completely disintegrated the Acid Black 210 dye into CO 2 and H 2 O within one hour. The high disintegrative capacity of the CuO nanoparticles is due to their crystalline nature, because studies have shown that the higher the crystalline nature, the higher the disintegrative ability and the disintegration rate [2,19].…”
Section: Discussionmentioning
confidence: 99%
“…These superoxide free radicals and hydroxyl free radicals react violently with Acid Black 210 organic dye and decompose/ decolorize it in the next step. The degradation/decomposition rate of the organic dye totally depends on morphological and crystal structure of the photochemical catalyst [2,19]. The active sites of photo-catalysts can be increased by increasing surface area and crystalline structure; these in turn increase the effectiveness of photo-catalytic reactions by separating electron-hole pairs [19].…”
Section: Photo-catalytic Dye Degradationmentioning
confidence: 99%
“…Adsorption is universally accepted and the most widely used method of water treatment as it involves the least sophisticated instrumentation with easy operations and can be operated with a wide range of adsorbents [16]. The simple design, nontoxic, eco-friendly, low cost adsorbents, treatment cost and mild conditions are criteria for selection of best mode and adsorbent [17]. Researchers have developed various organic and inorganic adsorbents for the removal of Pb(II) and Zn(II) ions from aqueous solutions.…”
Section: Sciencedirectmentioning
confidence: 99%
“…The morphology of the adsorbent particles was performed by scanning electron microscopy (JSM- 5510, Jeol Ltd., Tokyo, Japan) under an acceleration voltage of 30 kV. The XRD pattern of the fresh and used adsorbent was recorded by an automated X-ray diffracto-meter (Philips X’Pert, Netherlands) at the condition explained in the literature [17], [18]. The pHzpc factor was obtained using method specified by published studies [19], [20], [21], briefly; in the batch equilibrium method we used the ratio of 1:250 adsorbent to distilled water in 0.01 M NaCl solution, as an inert electrolyte.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%